PENGEMBANGAN NILAI-NILAI KESENIAN WAYANG JEMBLUNG UNTUK MEREDUKSI PROKRASTINASI AKADEMIK MAHASANTRI - Mudafiatun Isriyah; Weni Kurnia Rahmawati; Ghina Ghoida’ Al Khavi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
his study aims to develop the artistic values of Wayang Jemblung as an educational medium to reduce procrastination among university students. Academic procrastination often has negative impacts such as declining academic achievement, stress, anxiety, and feelings of guilt. Therefore, this research is intended to reduce academic procrastination by developing a product in the form of a guidance and counseling service module as a reference for addressing this issue. The development approach integrates the cultural and character aspects of Wayang Jemblung into a specially designed counseling guidance program. The study results show that utilizing traditional art values can significantly increase learning motivation and decrease task-procrastinating behavior. The implications of this research emphasize the importance of developing local culture as an effective strategy to address procrastination in academic environments. This research was conducted using the Research and Development (R&D) method, employing the ADDIE model. The outcome produced by the researcher is a guidance and counseling service module to manage procrastination by adopting the values embedded in Wayang Jemblung art. The research subjects involved female students and guidance counselors at Pondok Pesantren Ibnu Katsir Jember. Data were collected through observation, interviews, and questionnaires, and analyzed using qualitative and descriptive quantitative techniques.